2020
DOI: 10.1021/acs.jafc.0c00713
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Soluble Mono, Di, and Oligosaccharide Content in 23 Dry Beans (Phaseolus vulgaris L.)

Abstract: Beans provide a rich source of plant-based proteins and carbohydrates. It is well documented in the literature that the raffinose family of oligosaccharides (RFOs: raffinose, stachyose, and verbascose) is linked with flatulence issues. In this study, the soluble sugar content of 23 dry beans was investigated using a newly developed and validated analytical method with highperformance anion-exchange chromatography coupled to an amperometric pulse detection. All seven sugars (galactose, glucose, fructose, sucros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…It is likely that inherent soluble (free) sugars may also contribute to the sweetness of the pulses. Berrios et al (2010) and Kotha et al (2020) reported the presence and differing concentrations of glucose, ribose, fructose, galactose, sucrose, maltose, and ciceritol in raw pea, chickpea, lentil, and dry bean seeds. The different levels of these sugars may lead to differences in perceived sweetness among the pulses.…”
Section: Sweetnessmentioning
confidence: 99%
“…It is likely that inherent soluble (free) sugars may also contribute to the sweetness of the pulses. Berrios et al (2010) and Kotha et al (2020) reported the presence and differing concentrations of glucose, ribose, fructose, galactose, sucrose, maltose, and ciceritol in raw pea, chickpea, lentil, and dry bean seeds. The different levels of these sugars may lead to differences in perceived sweetness among the pulses.…”
Section: Sweetnessmentioning
confidence: 99%
“…For this purpose, an Agilent HPLC 1290 instrument (Agilent Technologies), coupled with a Thermo Scientific TSQ Vantage instrument (Thermo Fisher Scientific), operated by Xcalibur version 2.2 (Thermo Fisher Scientific), was used as described previously. 37 In brief, sugar identification was achieved using both the deprotonated molecule mass (m/z) and product ion masses using both data-dependent (MS 2 ) scans (DDS) [or data-dependent acquisition (DDA)] and Statistical Analysis. All colorimetric and spectroscopic analyses were performed in triplicate from each of the three plant samples (n = 9), and data expressed as the mean ± the standard deviation (SD) using Microsoft Excel.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…An LC-MS/MS method was used to confirm the identity of soluble sugars on a limited number of spinach samples from control and high-salinity treatments (T1, T5, T6, and T10). For this purpose, an Agilent HPLC 1290 instrument (Agilent Technologies), coupled with a Thermo Scientific TSQ Vantage instrument (Thermo Fisher Scientific), operated by Xcalibur version 2.2 (Thermo Fisher Scientific), was used as described previously . In brief, sugar identification was achieved using both the deprotonated molecule mass ( m / z ) and product ion masses using both data-dependent (MS 2 ) scans (DDS) [or data-dependent acquisition (DDA)] and selective ion monitoring (SIM) mode.…”
Section: Methodsmentioning
confidence: 99%
“…However, in human gut microbiome there are various microorganisms capable of digesting RFOs. Unfortunately, the fermentation of RFOs can result in production of carbon dioxide, hydrogen and methane, which are components causing flatulence 4 . There are many strategies used for the improvement of nutritional quality of lentils and beans, which have proven to be successful in decreasing concentration of RFOs, such as dehulling, germination, soaking (in alcohol or water), various heat-treatments (boiling, autoclaving, microwave cooking, extrusion), enzymatic treatment, irradiation or fermentation 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%